ANALISIS SIKAP WAJIB PAJAK TERHADAP TINGKAT KEBERHASILAN PENERIMAAN PBB - Daniel Akbar, 08.05.52.0189; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2012)
This study to know and analysis the effect of factors attached to the tax payerâs tax views of consciousness tax payer, the tax payer attitudes about the United Nations financial penalties, and the nations reception success rate in the district of Gunung Pati regency of Semarang.The population in this study is the UN tax payers in the district of Gunung Pati regency of Semarang. Samples were taken by 100 respondents to the proportional sampling methods, namely the number of tax payers in each village is divided by the total number of tax payer in the district and then multiplied by 100 ( number of sample taken ).The research results can be concluded that the results of the analysis indicate that factors inherent to the tax payer regarding the tax payer awareness of taxation (X1), the tax payer attitudes about the united nations financial penalties (X2), and the tax payerâs perception that the UN has been the general avoidance (X3) have partially positive and significant influence on the success rate of acceptance of the UN (Y).Key Words: Land and building tax, The tax payer